2018
DOI: 10.3390/ijms19113337
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Retinol Metabolism-Related Genes in an ANIT-Induced Cholestasis Rat Model

Abstract: Cholestasis is defined as a reduction of bile secretion caused by a dysfunction of bile formation. Insufficient bile secretion into the intestine undermines the formation of micelles, which may result in the reduced absorption of lipids and fat-soluble vitamins. Here, we investigated the retinol homeostasis and the alterations of retinol metabolism-related genes, including β-carotene 15,15′ monooxygenase (BCMO), lecithin:retinol acyltransferase (LRAT), aldehyde dehydrogenase (ALDH), cytochrome P450 26A1 (CYP26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
0
0
Order By: Relevance
“…Steroid hormone biosynthesis also promotes cholesterol conversion and bile acid synthesis, increasing cholesterol excretion from the liver ( Sun et al, 2021 ). The current study found that retinol metabolism was significantly inhibited in the livers of rats in the cholestasis model, which supports previous studies ( Cai et al, 2014 ; Takitani et al, 2018 ; Yuan et al, 2018 ). Retinoic acid may improve lipid deposition.…”
Section: Discussionsupporting
confidence: 92%
“…Steroid hormone biosynthesis also promotes cholesterol conversion and bile acid synthesis, increasing cholesterol excretion from the liver ( Sun et al, 2021 ). The current study found that retinol metabolism was significantly inhibited in the livers of rats in the cholestasis model, which supports previous studies ( Cai et al, 2014 ; Takitani et al, 2018 ; Yuan et al, 2018 ). Retinoic acid may improve lipid deposition.…”
Section: Discussionsupporting
confidence: 92%
“…Owing to their distinct chemical structure, bile salts possess surfactant/detergent-like properties and are important contributors to micellar solubilization of dietary lipids (mainly TAGs). The impairments of bile formation and secretion cause the reduction of bile salts secretion or obstruction of bile fl ow (which is called "cholestasis") [4] . Chronic cholestasis causes malabsorption of vital micronutrients [5] .…”
Section: Food Science and Human Wellnessmentioning
confidence: 99%